PENILAIAN VITALITAS POHON JATI DENGAN FOREST HEALTH MONITORING DI KPH BALAPULANG - lely Pratiwi S.; Rahmat Safe'i (Jurnal Ecogreen, 2018)
ABSTRACTThe aim of this study is to assess the vitality of trees as an indicator of forest health which consists of tree damage and tree canopy condition knowing the current state of health of the forest (status). This research was conducted in July - August 2017 at RPH Banjarharjo and RPH Malahayu, BKPH Banjarharjo Barat, KPH Balapulang, Central Java Regional Division Perum Perhutani. Data collection using sample method, Forest Health Monitoring (FHM) method and documentation. Damage of trees contained in BKPH Banjarharjo actually very small but because the assessment is done in the dry season so many found damage to the leaves of the tree. The CLI values are successively from cluster plot 1 and cluster plot 2 that is 2,2 and 3,4. At the VCR values successive cluster plots 1 and plot 2 clusters are 3.5 and 3.4. The results show that the current state of forests (status) is moderate. Keywords: tree, forest health, status.